The Moderating Role of Decent Work on the Relationship Between Turnover Intention and Job Performance Among Commercial Banks in Zimbabwe - Nhamo, Mashavira; Mildred, Mahapa (Journal of Islamic Economics and Business, 2023)
The challenges of staff retention and job performance persist as significant concerns for businesses, particularly in the context of Zimbabwe. While numerous studies have explored the impact of turnover intention on job performance, there is a gap in understanding the moderating variables influencing this relationship. This research aims to investigate the nuanced connection between decent work, intentions to leave, and job performance in the Zimbabwean banking sector, utilizing a quantitative approach with a causal design. The findings reveal a significant relationship between turnover intention and job performance. Moreover, it is deduced that all four pillars of decent work act as moderators in the association between turnover intention and job performance within the commercial banking sector in Zimbabwe.